A complete career change from creative to classroom, learning to become an RVN. Issue 1 (5th February 2021) - Curtis, Sally
ABSTRACT: In a more personal series of VNJ features on career path experiences from within the veterinary nursing profession, we begin with an unusual career change story from interiors stylist to Student Veterinary Nurse. This shows how diverse veterinary nurse backgrounds can be and how life experience can help with managing such a variable role.